Analysis of the Effect of Liquidity Ratio on Net Profit Margin at PT. Unilever Indonesia Tbk Report Year 2018-2022 - Nirmalasari Nirmalasari (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine the effect of Liquidity Ratio on Net Profit Margin at PT Unilever Reporting Year 2018-2022. This type of research is quantitative research. The population in this study is the financial statements of PT Unilever Indonesia Tbk 2018-2022 which are listed on the Indonesia Stock Exchange (IDX) which have been published. The samples in this study are the company's current assets and net profit margin. The results showed that the obtained tcount value = 3.049 which means tcount> ttable (3.049> 2.045) with a significant 0.003 <0.05 then Ha is accepted and H0 is rejected, meaning that the hypothesis (H1) shows the results of the current ratio has a positive and significant effect on net profit margin at PT Unilever Indonesia Tbk. Simultaneously obtained F count = 6.099 and the results obtained for the F table are 4.17 So the results of the calculation of Fhitung ˃ Ftabel (6.099> 4.i7 with a sig value obtained (0.000 ˂ 0.05) then simultaneously the independent variable current ratio has a positive and significant effect on PT. Unilever Indonesia Tbk.